Purpose and potential for commodity exchanges in African economies - Rashid, Shahidur; Winter-Nelson, Alex; Garcia, Philip (International Food Policy Research Institute, 2010)
This paper reviews the purpose and potential of commodity exchanges in Africa. Drawing from the existing literature and using indicative empirics, it examines the conditions that enable successful exchanges, highlights the special challenges to setting up exchanges in Africa, and reviews alternatives to domestic exchanges. We argue that many critical preconditions for the successful establishment of commodity exchanges in Africa remain binding in the short to medium term. The development of commodity exchanges in the region is impeded by the relatively small size of domestic commodity markets, the weak physical and communication infrastructure, a lack of supportive legal and regulatory environments, and the likelihood of policy interventions, particularly in the staple cereals market. Meanwhile, the demand for a domestic commodity exchange for export crops may be limited due to the availability of well-established exchanges abroad and functioning auction floors. The paper highlights three points: (a) efforts to launch exchanges in Africa should realistically assess whether basic conditions for success can be met, (b) if the pre-conditions cannot be met, the use of existing exchanges abroad or the development of regional exchanges may be more feasible than the establishment of national commodity exchanges, and (c) the goals of risk management and reduced transaction costs might be achieved more effectively by improving market fundamentals through investments in transportation, information services, or other financial institutions.